Synchrophasor‐based system integrity protection scheme for an ultra‐mega‐power project in India. Issue 8 (28th February 2019) - Kumar, Deepa S.; Savier, J.S.
Abstract : System Integrity Protection Scheme (SIPS) aids the normal protection scheme in case of certain special contingencies like tripping of important corridors/flow gates etc. to mitigate the voltage or angular instability, load generation imbalance and finally large‐scale cascading catastrophes. A recent blackout incident in an ultra‐mega‐power project (UMPP) in India has motivated the authors to ponder upon a SIPS as a solution. As part of designing the SIPS, an efficient solution is formulated using synchrophasors for a well‐known issue nonetheless an issue which still disturbs the Indian power system network with blackouts – i.e. unintended distance relay operation in the event of power swing. Here, real‐time voltage and current phasors and the angular separation between the buses connecting faulted line, acquired by phasor measurement unit is utilised to derive a differential power coefficient (DPC). This study proposes a modified logic scheme for blocking/de‐blocking of distance relays i.e. change the existing scheme with 'block all zones except Zone‐1' to 'block all zones on power swing detection'. Rate of change of DPC is derived here which aids in differentiating stable and unstable power swings. A special protection scheme is finally formulated based on the modified logic.